Nanomaterial Complexes Enriched With Natural Compounds Used in Cancer Therapies: A Perspective for Clinical Application - Saavedra-Leos, María Zenaida; Jordan-Alejandre, Euclides; López-Camarillo, César; Pozos-Guillen, Amaury; Leyva-Porras, César; Silva-Cázares, Macrina Beatriz (Frontiers in Oncology, 2021)
Resveratrol and quercetin are natural compounds contained in many foods and beverages. Reports indicate implications for the health of the general population; on the other hand the use of both compounds has interesting results for the treatment of many diseases as cardiovascular affections, diabetes, Alzheimer’s disease, viral and bacterial infections among others. Based on their capacities described as anti-inflammatory, antioxidant, and anti-aging, resveratrol and quercetin showed antiproliferative and anticancer activity specifically in maligned cells. These molecular characteristics trigger the pharmacological repurposing of both compounds and improved its research for treating different cancer types with interesting results at in vitro, in vivo, and clinical trial studies. Meanwhile, the development of different systems of drug release in specific sites as nanomaterials and specifically the nanoparticles, potentiates the personal treatment perspective in conjunct with the actual cancer therapies; regularly invasive and aggressive, the perspective of nanomedicine as higher effective and lower invasive has gained popularity. Knowledge of molecular interactions of resveratrol and quercetin in diseases confirms the evidence of multiple benefits, while the multiple analyses suggested a positive response for the treatment and diagnostics of cancer in different stages, including at metastatic stage. The present work reviews the reports related to the impact of resveratrol and quercetin in cancer treatment and its effects when the antioxidants are encapsulated in different nanoparticle systems, which improve the prospects of cancer treatment.